Hubungan Antara Pembinaan Iman Dengan Resiliensi Pada Remaja Katolik Di Smk Santo Fransiskus Semarang - Elisabeth Marito Gultom; Sugiyana Sugiyana; Wuriningsih Wuriningsih (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2022)
Adolescence is when a person begins to learn to be an adult human being. Therefore, there is a need for coaching. On the other hand, adolescence also experiences resilience. For this reason, faith formation is needed. This also happened to the students of St. Fransiskus Vocational School Semarang. Therefore, faith-building at St. Fransiskus Vocational School affects student resilience. To discuss this problem, the researcher conducted a study entitled The Correlation Between Faith Development and Resilience in Catholic Adolescents at St. Fransiskus Vocational School Semarang as the subject of the study was a Catholic student at St. Fransiskus Vocational School Semarang. The method used is descriptive quantitative with correlational techniques. This research was conducted from July to September 2021. The variables of this research are independent variables of Catholic faith development and dependent variables of adolescents. The research population was all St. Fransiskus Vocational School Semarang students, and samples were taken using simple random sampling techniques. The theoretical basis used is the theory of faith development and adolescent resilience. The results showed that the calculated r-value (rxy) was 0.6373, which was included in the relatively strong or high category (the calculated r-value was 0.41 - 0.70). Based on the data analysis, it was concluded that there is a correlation between faith development and resilience in Catholic adolescents at St. Fransiskus Vocational School in Semarang. The percentage of contribution of faith development to resilience in Catholic adolescents at St. Fransiskus Vocational School Semarang is 40.61%, based on calculations using the product-moment correlation formula.